USING COGNITIVE LINGUISTICS TO TEACH SYNONYMS FOR IRAQI COLLEGE STUDENTS - Albaidhani, Mareb (Al-Adab Journal, 2023)
It's challenging to help EFL students in Iraq learn and use synonyms. This study investigates the challenges faced by Iraqi English as a Foreign Language (EFL) students in understanding and employing synonyms. By employing Langacker's cognitive linguistic theory of domains, the research aims to enhance EFL Iraqi students' synonym knowledge and vocabulary acquisition. The study utilizes a descriptive analysis technique, with a pre-test and post-test design, involving fifty first-year students at the University of Baghdad's College of Languages, Department of English. The findings reveal that the domain theory significantly improved students' comprehension and application of English word semantics. Prior to the intervention, students had limited knowledge of the domain approach and struggled with recognizing and producing lexical features. After five weeks of treatment, students demonstrated increased abilities to define different types of domains and their properties, as well as understanding the literal and conceptual meanings of words. The study concludes that implementing the theory of domains can effectively enhance vocabulary acquisition among Iraqi EFL students and emphasizes the importance of teaching synonyms with a focus on sense relations.